Freed Imperial Court-Affiliated Slaves and Their Former Masters in the Early Modern Ottoman World: The Role of the Velâ Relationship (17th–18th Centuries) - ARGIT, FATMA BETÜL (My University, 2021)
Copyright © 2021 Ottoman and Turkish Studies Association.According to Islamic law, upon manumission a freed slave immediately attained the same full legal rights vis-à-vis the other, freeborn members of society. Yet the former slave remained in a special relationship with his/her former master, called velâ (ar. walā’) or patronate. The manumitted person and his/her descendants remained bound for life to the manumitter and his/her lineal heirs through this velâ relationship, as it regulated the ongoing rights of and duties between the two parties. For example, velâ mandated the inheritance relationship between the manumitter and the freed person, entitling the manumitter and his/her lineal heirs to the freed person’s inheritance on the condition that the latter had no surviving male agnatic relatives. Using Istanbul Shari’a court records, and particularly the registers of inheritance and estate inventories for the seventeenth and eighteenth centuries, this article demonstrates how the velâ arrangement worked in practice. Through a close study of the inheritance records related to slave-origin male and female members of the imperial court, it analyses how and in what ways the inheritance relationship was realized between freed Ottoman imperial court-affiliated slaves and their former masters. It also demonstrates how imperial court affiliation impacted the velâ relationship. This article suggests that unpacking the velâ institution contributes to a better understanding of the social, economic and cultural aspects of slavery in the Ottoman world.
Keywords: Sosyal ve Beşeri Bilimler; Tarih; Sosyoloji; Antropoloji; İlahiyat; Hukuk; Social Sciences and Humanities; History; Sociology; Anthropology; Theology; Law; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; Sosyal Bilimler Genel; ANTROPOLOJİ; KÜLTÜREL ÇALIŞMALAR; DİN; TARİHÇE; KANUN; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; SOCIAL SCIENCES, GENERAL; ANTHROPOLOGY; CULTURAL STUDIES; RELIGION; HISTORY; LAW; Kültürel çalışmalar; Sosyal Bilimler ve Beşeri Bilimler; Dini çalışmalar; Cultural Studies; Social Sciences & Humanities; Religious Studies